A longitudinal study of free leptin index in pre‐eclamptic pregnancies. Issue 8 (23rd March 2023) - Garcés, María Fernanda; Buell‐Acosta, Julieth Daniela; Rodríguez‐Navarro, Haiver Antonio; Páez‐Leal, María Carolina; Maldonado‐Acosta, Luis Miguel; Peralta‐Franco, Jhon Jairo; Burgos‐Cardenas, Álvaro Javier; Ángel‐Müller, Edith; Parada‐Baños, Arturo José; Parra‐Pineda, Mario Orlando; Eslava‐Schmalbach, Javier; Escobar‐Sarmiento, Camilo Andrés; et al.
Abstract: The ratio between circulating levels of leptin and soluble leptin receptor (sOB‐R), the free leptin index (FLI), is used as a marker of leptin resistance. Therefore, the aim of our study was to investigate the FLI in mild pre‐eclamptic pregnancies in a nested case–control study within a prospective observational study. Circulating levels of leptin and sOB‐R levels rise significantly during pregnancy in healthy ( p < 0.05) ( n = 46) and pre‐eclamptic pregnancies ( p < 0.05) ( n = 20). Serum levels of leptin were significantly higher in pre‐eclamptic compared to healthy pregnancies at second and third trimesters of pregnancy ( p < 0.05). Additionally, serum levels of sOB‐R were significantly lower in pre‐eclamptic pregnancies during the second and third trimesters of pregnancy compared to healthy pregnancies ( p < 0.05). Moreover, we found that FLI did not vary significantly during pregnancy in healthy women ( p > 0.05), while it increases in pre‐eclamptic pregnancies ( p < 0.05). Indeed, FLI was significantly higher at second and third trimesters of pregnancy in pre‐eclamptic compared to healthy pregnancies ( p < 0.05). In addition, FLI was significantly higher in the luteal phase compared with the follicular phase of the menstrual cycle in eumenorrheic women ( p < 0.05). Receiver operating characteristic (ROC) curve analysis revealed the ability of leptin (AUC = 0.72) and FLI (AUC = 0.67) as a reliable predictor for mild pre‐eclampsia during the second trimester of pregnancy. In conclusion, our findings show that FLI were significantly increased in mild pre‐eclamptic pregnancies and allowed us to hypothesize that this rise might alter leptin bioavailability and bioactivity which might lead to the sympathetic hyperactivity and the hypertensive disorders during pregnancy.